KOMUNIKASI POLITIK CALEG MILENIAL : (STUDI KASUS TIGA CALON ANGGOTA LEGISLATIF PADA PEMILIHAN ANGGOTA LEGISLATIF KABUPATEN SRAGEN TAHUN 2024) - Dyah Paradita, Rheinova Kirana; Itasari, Andri Astuti; Maserona, Lukas (Solidaritas, 2025)
This study aims to disseminate political communication implemented by millennial legislative candidates (caleg) in the 2024 Legislative Election (Pileg) campaign in Sragen Regency. Given the large contribution of the millennial generation in the election, which covers around 33% of the total votes (Lemhannas RI, 2024), this study highlights the importance of an effective political communication strategy to attract the attention of young voters. This study uses a qualitative approach with an in-depth interview method with three millennial legislative candidates, Nugroho Sulistyo, Bakti Ida Hutami, and Ria Cerryana Rahmawati, as well as first-time voters who represent support for each legislative candidate. The results of the study show that social media plays a very important role in shaping the political views of millennial voters, with platforms such as Instagram, TikTok, and WhatsApp used by legislative candidates to convey their political messages. Issues such as education, economic welfare, and infrastructure development are the main focus of their campaigns, which are relevant to the daily lives of young voters. Overall, this study found that effective political communication through social media, as well as communicating messages that are in line with the issues faced by young voters, are important factors in winning support in the 2024 Election. Keywords: Political Communication, Millennial Candidates, Social Media, First-Time Voters.